Biased allosteric modulation at the CaS receptor engendered by structurally diverse calcimimetics - Cook, A E (Br J Pharmacol, 2015)
BACKGROUND AND PURPOSE: Clinical use of cinacalcet in hyperparathyroidism is complicated by its tendency to induce hypocalcaemia, arising partly from activation of calcium-sensing receptors (CaS receptors) in the thyroid and stimulation of calcitonin release. CaS receptor allosteric modulators that selectively bias signalling towards pathways that mediate desired effects [e.g. parathyroid hormone (PTH) suppression] rather than those mediating undesirable effects (e.g. elevated serum calcitonin), may offer better therapies. EXPERIMENTAL APPROACH: We characterized the ligand-biased profile of novel calcimimetics in HEK293 cells stably expressing human CaS receptors, by monitoring intracellular calcium (Ca(2+)(i)) mobilization, inositol phosphate (IP)(1) accumulation, ERK1/2 phosphorylation (pERK1/2) and receptor expression. KEY RESULTS: Phenylalkylamine calcimimetics were biased towards allosteric modulation of Ca(2+)(i) mobilization and IP(1) accumulation. S,R-calcimimetic B was biased only towards IP(1) accumulation. R,R-calcimimetic B and AC-265347 were biased towards IP(1) accumulation and pERK1/2. Nor-calcimimetic B was unbiased. In contrast to phenylalkylamines and calcimimetic B analogues, AC-265347 did not promote trafficking of a loss-of-expression, naturally occurring, CaS receptor mutation (G(670)E). CONCLUSIONS AND IMPLICATIONS: The ability of R,R-calcimimetic B and AC-265347 to bias signalling towards pERK1/2 and IP(1) accumulation may explain their suppression of PTH levels in vivo at concentrations that have no effect on serum calcitonin levels. The demonstration that AC-265347 promotes CaS receptor receptor signalling, but not trafficking reveals a novel profile of ligand-biased modulation at CaS receptors The identification of allosteric modulators that bias CaS receptor signalling towards distinct intracellular pathways provides an opportunity to develop desirable biased signalling profiles in vivo for mediating selective physiological responses.